Effects of central irisin administration on the uncoupling proteins in rat brain - Erden, Yavuz; Tekin, Suat; Sandal, Suleyman; Onalan, Ebru Etem; Tektemur, Ahmet; Kirbag, Sevda (Elsevier Ireland Ltd, 2016)
Irisin is a thermogenic peptide that enables the development of brown adipose tissue from white adipose tissue by activating the UCP1. This study has been designed to determine the effects of the irisin on UCPs. Sprague Dawley female rats were used in the study. 1, 3 and 10 mu M concentrations of irisin were injected intracerebroventricularly to the rats, and the control group was received only vehicle. The animals were killed at the 16, 24, and 48 h time intervals and their brains were taken out. The hypothalamus, pituitary gland, hippocampus, cerebellum, striatum and cortex areas were separated and the UCP2, UCP3, UCP4 and UCP5 mRNA levels were determined. Just before the animals were killed, their body temperatures were recorded. It was observed that after application of the high dose irisin, UCP5 mRNA level in the all brain areas increased (p < 0.05); it was also observed that the three doses decreased the UCP4 expression in all brain areas (except the pituitary gland; p < 0.05). The UCP2 and UCP3 mRNA expressions showed significantly increase in cerebellum and striatum (p < 0.05). The UCP2 mRNA expression decreased in hypothalamus, pituitary gland, hippocampus and cortex areas (p < 0.05). It was also observed that the body temperatures of the rats increased depending on the irisin injection and this increase was the most considerable at the 24h (p < 0.05). The results of this study suggest that the UCP2-5 is expressed in different areas of the brain, and the irisin affects this expression, and may have effective roles in some brain functions. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Irisin; UCP2; UCP3; UCP4; UCP5; Rat brain; Body temperature